Concept confirmation of the Treatment Administration Satisfaction Questionnaire (TASQ) in rare paroxysmal nocturnal hemoglobinuria - Helen Doll; Ufuk Coşkun; Chris Hartford; Ioannis Tomazos (SpringerOpen, 2021)
Abstract Background This study was conducted to evaluate content validity of the IntraVenous and SubCutaneous Treatment Administration Satisfaction Questionnaires (TASQ-IV and TASQ-SC), for use in a clinical trial population of participants with paroxysmal nocturnal hemoglobinuria (PNH) undergoing eculizumab treatment. Methods Participants underwent semi-structured combined brief introduction to disease history and full cognitive debriefing interviews to establish symptoms and key impacts of PNH and to explore the clarity and relevance of both sets of instructions (TASQ-IV and TASQ-SC). The clarity, relevance, response options, and recall period of the TASQ-IV items were also explored. Results Ten participants with PNH were recruited. Fatigue was the most commonly reported symptom (n = 7); the most commonly reported impact of PNH was on physical activity (n = 4). Nine participants indicated understanding and relevance of the TASQ-IV instructions; three participants suggested changes. Of the 20 TASQ-IV items, ≥ 15 were considered understandable, relevant and to have suitable response options (n ≥ 8). The TASQ-SC instructions were understood by all participants; seven participants indicated relevance. While a few participants suggested minor changes for the items, these reflected the one-off completion of the measure in an interview setting and were thus not considered sufficient to justify modification of the measure for clinical trial completion. Conclusions Most participants understood the TASQ-IV and TASQ-SC instructions (n = 9 and 10, respectively) and the TASQ-IV items were considered clear, relevant and to have suitable response options, demonstrating face and content validity of the instruments for the clinical trial setting.